Examining the Entrepreneurial Perspective and Performance of ‘Indigenous’ Domestic Manufacturing Firms in Kano State, Nigeria. - Sani, Muhammad Baffa; Muhammad, Ibrahim Garba; Mu’azu, Mu’azu Hassan (Research in Management of Technology and Business, 2022)
This study examines relationship between entrepreneurial perspective (EP) and performance of ‘indigenous’ domestic manufacturing firms (IMFs) in Kano State, Nigeria, using multiple regression models. A survey method was adopted. Questionnaire instrument was administered on a census based sampling of 179 IMFs. 152 copies (85%) of the administered questionnaire were returned. However, due to data screening and cleaning, analysis was made on 125 IMFs (70% of total copies of questionnaire distributed). The study discovers strictness to routine significantly affects the IMFs’ performance. Statistically, it influences performance by 57.3%. Thus, this study recommends the IMFs-on individual basis-to acquire managing change skills; frequent management trainings to be regularly organised by their associations; join hands to wholly pursue policies that promote and protect private sector interests. In addition, to reconfirm the authenticity and implication of EP on firm performance, study to examine relationship between the EP and the closed IMFs, in the same study area is highly suggested by this research. The study would give insight as regards relatedness to the closure of the firms.